2015
DOI: 10.1007/s10549-015-3487-z
|View full text |Cite
|
Sign up to set email alerts
|

Fat/water ratios measured with diffuse reflectance spectroscopy to detect breast tumor boundaries

Abstract: Recognition of the tumor during breast-conserving surgery (BCS) can be very difficult and currently a robust method of margin assessment for the surgical setting is not available. As a result, tumor-positive margins, which require additional treatment, are not found until histopathologic evaluation. With diffuse reflectance spectroscopy (DRS), tissue can be characterized during surgery based on optical parameters that are related to the tissue morphology and composition. Here we investigate which optical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 45 publications
4
71
0
Order By: Relevance
“…Technical advances in the treatment of liver malignancies, such as laparoscopic and robotic surgery as well as more frequent administration of neo-adjuvant systemic treatment, call for new technologies aiding the surgeon to correctly locate and resect the entire tumor volume in the liver. In previous studies, we have shown that DRS and FS can be used to identify various types of tissue in ex vivo experiments in lung and breast [8,22,23]. Also in liver tissue, we have demonstrated that DRS can accurately discriminate normal liver tissue from CRLM in an ex vivo model with a sensitivity and specificity of 94% [12].…”
Section: Discussionmentioning
confidence: 88%
“…Technical advances in the treatment of liver malignancies, such as laparoscopic and robotic surgery as well as more frequent administration of neo-adjuvant systemic treatment, call for new technologies aiding the surgeon to correctly locate and resect the entire tumor volume in the liver. In previous studies, we have shown that DRS and FS can be used to identify various types of tissue in ex vivo experiments in lung and breast [8,22,23]. Also in liver tissue, we have demonstrated that DRS can accurately discriminate normal liver tissue from CRLM in an ex vivo model with a sensitivity and specificity of 94% [12].…”
Section: Discussionmentioning
confidence: 88%
“… It has been reported that extended NIR wavelength region measurement renders a better discrimination between benign and tumor sites as well as accurate estimation of chromophores present in the tissue. Recently, detection of classical WAT and BAT in vivo using optical techniques, such as diffuse optical spectroscopy and imaging (DOSI) or time resolved spectroscopy, was reported. In one of these studies, Ganesan et al used DOSI to detect the changes in subcutaneous adipose tissue during weight loss in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research, one of the main differences in optical properties between tumor and healthy breast tissue is the higher water and lower fat content in tumors compared to healthy tissue . Therefore, we focused on the NIR wavelength range, where water and fat are the main absorbers of light.…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the optical penetration depth and diffuse reflectance in breast tissue using known optical properties of breast tissue . Since water and fat are the main absorbers of light in the NIR region, equations for the absorption coefficient and the reduced scattering were approximated by: μa()λ=εwater()λ[]water+εfat()λ[]fat μs()λ=μnormals,800λ8000.25emnmb In which [water] and [fat] represent the water and fat concentration in the tissue, and ε water and ε fat their extinction spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation